STUDENTS’ STRATEGIES IN PARAPHRASING AN ENGLISH TEXT: paraphrasing - nur istiroqah sanjaya (Universitas Hasanuddin, 2021)
The purpose of this study is to identify strategies used by students in paraphrasing. The sample of this study was 25 students in the fifth semester in the faculty of literature at the Muslim University of Indonesia. The benefits of this research are expected to be a reference for lecturers to develop the material being taught and for students to recognize their abilities in paraphrasing so that they can practice more. Therefore, qualitative descriptive was applied to this study, while the data obtained was a paraphrasing test. This study indicates that most of the students use synonyms followed by condensing the original text. However, not infrequently, students substitute synonyms with the same meaning but different usage, thus making the meaning of the paraphrasing text ambiguous.